2016
DOI: 10.1038/srep26601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consecutive monoculture of Pseudostellaria heterophylla on soil fungal community as determined by pyrosequencing

Abstract: Under consecutive monoculture, the biomass and quality of Pseudostellaria heterophylla declines significantly. In this study, a three-year field experiment was conducted to identify typical growth inhibition effects caused by extended monoculturing of P. heterophylla. Deep pyrosequencing was used to examine changes in the structure and composition of soil fungal community along a three-year gradient of monoculture. The results revealed a distinct separation between the newly planted plot and the two-year, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 42 publications
10
39
1
1
Order By: Relevance
“…Our field experiment showed that consecutive monoculture of P. heterophylla resulted in a significant decline in the yield of tuberous roots ( Figure 2 ). Many factors have been thought to be responsible for the consecutive monoculture problem of P. heterop hylla, including soil physical and chemical properties, accumulation of allelochemicals released by roots, and shifts in the soil microbial community (Wu L. et al, 2016). In this study, we found that the content of most of the soil nutrients were significantly higher in the unhealthy samples (SP and MO) than in the healthy samples (NP and MT) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our field experiment showed that consecutive monoculture of P. heterophylla resulted in a significant decline in the yield of tuberous roots ( Figure 2 ). Many factors have been thought to be responsible for the consecutive monoculture problem of P. heterop hylla, including soil physical and chemical properties, accumulation of allelochemicals released by roots, and shifts in the soil microbial community (Wu L. et al, 2016). In this study, we found that the content of most of the soil nutrients were significantly higher in the unhealthy samples (SP and MO) than in the healthy samples (NP and MT) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies by culture-dependent and culture-independent analysis demonstrated that F. oxysporum and other Fusarium spp. are the main causative agents of wilt and rot disease of this plant (Zhao Y. et al, 2015; Wu L. et al, 2016). Our previous studies have demonstrated that the phenolic acids identified in the root exudates of P. heterophylla could significantly inhibit the growth of beneficial Burkholderia sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations